2021
DOI: 10.35848/1347-4065/ac0c6c
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric photovoltaic tensor in visible-light-active Fe-doped BaTiO3single crystals

Abstract: We investigate the photovoltaic currents as a function of light polarization angle for Fe-doped BaTiO 3 ferroelectric single crystals to elucidate the photon energy hv (2.5-3.1 eV) dependence of the bulk photovoltaic tensor elements (b 31 and b 33 ). The fitting analysis for the reduced sample in the Fe 2+ -and Fe 3+ -coexisting state reveals that | | b 31 and | | b 33 are reduced with decreasing hv while | | | | b b > 31 33 appears at hv above 2.8 eV. Densityfunctional theory calculations along with electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…We have reported that the bulk PV effect of transition metal-doped ferroelectric oxides is much larger than that of undoped crystals, especially in the visible light region with h¯< E g . 43), 109) We have presented that the 'gap state', which is an impurity level derived from dopant elements, acts as an active center for photocarrier generation. In the case of Mn-doped BFO, doubly degenerate electron-half-occupied gap states originating from Mn-3d orbitals are formed at 1.81.9 eV below the conduction band minimum [Fig.…”
Section: Gap-state Engineeringmentioning
confidence: 99%
“…We have reported that the bulk PV effect of transition metal-doped ferroelectric oxides is much larger than that of undoped crystals, especially in the visible light region with h¯< E g . 43), 109) We have presented that the 'gap state', which is an impurity level derived from dopant elements, acts as an active center for photocarrier generation. In the case of Mn-doped BFO, doubly degenerate electron-half-occupied gap states originating from Mn-3d orbitals are formed at 1.81.9 eV below the conduction band minimum [Fig.…”
Section: Gap-state Engineeringmentioning
confidence: 99%
“…2) The enhancement of the bulk PV effect by doping of impurity atoms has been experimentally observed in various ferroelectric materials. 8,11,13,[27][28][29][30] We found that Mn doping on the Fe site of ferroelectric BFO enhances the bulk PV effect, especially under visible light with photon energy (hν) lower than the bandgap energy (E g ). 31) Density functional theory calculations for Mn-doped BFO have indicated that gap states half-filled with electrons derived from Mn-3d orbitals are formed within the bandgap and also that the enhanced visible light activity arises from a two-step photoexcitation.…”
Section: Introductionmentioning
confidence: 97%
“…The unique feature of spontaneous polarization in BT has attracted researchers from diverse fields such as ferroelectricity, piezoelectricity, photovoltaics, etc. [1][2][3][4][5][6] For instance, the spontaneous polarization leads to a higher dielectric constant in BT ceramics because of which BTbased ceramics are important dielectric components of multilayer ceramic capacitors (MLCCs). 7) With the advancement in technology, the dielectric materials used in MLCCs are rigorously investigated to fulfill the demands of future applications.…”
Section: Introductionmentioning
confidence: 99%